Discovering the Traits of Personality in Anesthesiologists at Different Stages of Emotional Burnout Syndrome - Kokoshko, Alexey; Nurilya Maltabarova, Nurilya; Abduldayeva, Aigul; Smailova, Galiya; Shanazarov, Nasrulla (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
To date, intensive care medicine, anesthesiology, and resuscitation are medical spheres that deal with lifesaving issues, particularly the treatment of patients in critical or life-threatening situations. The profession of anesthesiologist-resuscitator is relatively new, although it has centuries-old prehistory. The study aims to identify personality traits that predispose to the formation of emotional burnout syndrome in anesthesiologists-resuscitators. The research was performed at the Anesthesiology and Resuscitation Departments of the regional healthcare facilities in Astana and Akmola cities. Findings obtained through this research confirm the hypothesis that personality traits in anesthesiologists-resuscitators are factors that facilitate the development of emotional burnout syndrome. Such a discovery necessitates the prevention of personality destructions as well as the establishment of conditions to reduce them in the case of occurrence. Proper arrangement of the work schedule and a favorable working environment allows preventing the emotional burnout among employees.